The charm offensive : a novel - Cochrun, Alison (Atria Paperback, 2021)
"Ever since he was a kid, Dev Deshpande has believed in fairy tales, and he has spent his career crafting them for the reality dating show Ever After. As the most successful producer in the franchise's history, Dev always scripts the perfect love story for his contestants, even as his own love life crashes and burns off-screen. That is, until the show casts disgraced tech wunderkind Charlie Winshaw as its star. Charlie is far from the romantic Prince Charming he's playing on TV. He doesn't believe in love (at least not for himself), and his publicist only agreed to the show as a last-ditch effort to rehabilitate his image. In front of the cameras, he's a stiff, anxious mess with no idea how to date thirty women on national television. Behind the scenes, he's cold, awkward, and emotionally closed-off. Only Dev can save the season--and possibly the entire show--by coaching Charlie through every scene. Dev always gets a happy ending, and he knows he can find a way to help Charlie find his. Yet the more Dev fights to get Charlie to open up to the contestants, the more they begin to open up to each other, and it soons becomes clear Charlie has better chemistry with Dev than with any of his female co-stars. Travelling to romantic locations around the world, they begin to suspect they could both find their happily ever after if they're willing to let go of their ideas about whose love story gets told"--